Directed Gas Phase Formation of the Elusive Silylgermylidyne Radical (H3SiGe, X2A′′). Issue 2 (16th December 2020) - Yang, Zhenghai; Doddipatla, Srinivas; Kaiser, Ralf I.; Krasnoukhov, Vladislav S.; Azyazov, Valeriy N.; Mebel, Alexander M.
Abstract: The previously unknown silylgermylidyne radical (H3 SiGe; X 2 A′′) was prepared via the bimolecular gas phase reaction of ground state silylidyne radicals (SiH; X 2 Π) with germane (GeH4 ; X 1 A1 ) under single collision conditions in crossed molecular beams experiments. This reaction begins with the formation of a van der Waals complex followed by insertion of silylidyne into a germanium‐hydrogen bond forming the germylsilyl radical (H3 GeSiH2 ). A hydrogen migration isomerizes this intermediate to the silylgermyl radical (H2 GeSiH3 ), which undergoes a hydrogen shift to an exotic, hydrogen‐bridged germylidynesilane intermediate (H3 Si(μ‐H)GeH); this species emits molecular hydrogen forming the silylgermylidyne radical (H3 SiGe). Our study offers a remarkable glance at the complex reaction dynamics and inherent isomerization processes of the silicon‐germanium system, which are quite distinct from those of the isovalent hydrocarbon system (ethyl radical; C2 H5 ) eventually affording detailed insights into an exotic chemistry and intriguing chemical bonding of silicon‐germanium species at the microscopic level exploiting crossed molecular beams. Abstract : Elusive radical : The previously unexplored silylgermylidyne radical (H3 SiGe) is synthesized in the gas phase through silicon‐germanium bond linkage of the silylidyne radical (SiH) with germane (GeH4 ) under single collision conditions.